Optimization of backpack loads using gait parameters in school boys. (January 2021) - Rashid, Muhammed; Mathew, Jerin; Raj V, Vijay Samuel; Raja, Kavitha
Abstract: Background: Backpacks are an efficient way of manual carriage used by people of all ages, and is commonly used by schoolchildren. Carrying heavy backpacks may result in cumulative trauma later in life due to biomechanical adaptations during gait. Gait parameters are known to be sensitive to force vectors, which can be altered by load carrying. This study attempts to find the most favorable backpack weight using gait changes as an indicator. Methods: This was an observational study conducted on twenty typically developing boys aged between 9 and 14 years. Gait analysis was done using standard recommendations, with increasing backpack loads with respect to their body weights. Gait cycles were captured using video cameras and analyzed using Kinovea0.8.25 motion analyzing software. Results: As the backpack load increased, significant kinematic changes were noted in the child's ankle, knee, and hip joints. These changes were evident when the backpack load increased beyond 15% of their body weight. Conclusions: This study concludes that the optimum weight that can be carried without having an impact on dynamic posture will be less than 15% of the body weight. Highlights: Significant changes were noted in all events of the gait cycle. The proximal joints exhibited greater changes than distal joints with an increase in weights. Maximum variation was observed when the load exceeded 15% of the body weight.